1981
DOI: 10.1139/z81-007
|View full text |Cite
|
Sign up to set email alerts
|

Limb regeneration in adult amphibia

Abstract: This paper reports a histological analysis of limb regeneration capacity in 20 species of amphibians. These data, along with a survey of other species reported in the literature, are used as a basis for the following generalizations. (1) Limb regeneration in the amphibians is not an all-or-none process, but regenerative capacity covers a continuum from normal regeneration to total absence of regenerative ability. (2) In adult anurans, regenerative outgrowth is common in discoglossids and pipids, occurs frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…3), malformed regenerates in fish fins (4), and hypomeric, nonfunctional outgrowths in amphibians (12). However, we found that species with superficially similar amputation outcomes can vary dramatically in the extent to which regeneration has been abrogated.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…3), malformed regenerates in fish fins (4), and hypomeric, nonfunctional outgrowths in amphibians (12). However, we found that species with superficially similar amputation outcomes can vary dramatically in the extent to which regeneration has been abrogated.…”
Section: Discussionmentioning
confidence: 79%
“…Although many animals capable of agametic reproduction have extraordinary regenerative abilities (21), and asexual and regenerative developmental processes can overlap substantially (1,11,25), naidines clearly demonstrate that regeneration is far from universal among agametically reproducing species, even in species, such as naidines, in which agametic reproduction is derived from regeneration (26). Furthermore, naidines join the small but growing list of examples showing that loss of regenerative abilities is not necessarily accompanied by large-scale changes in morphological complexity (2,4,5,12). Naidines all share a similar body plan, and species that cannot regenerate do not differ in any consistent way from fully regenerating species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In some species the fins can largely regenerate and also part of the eye, optic nerve, heart, and spinal cord (Cuervo, Hernandez‐Martinez, Chimal‐Monroy, Merchant‐Larios, & Covarrubias, ; Nakatani, Kawakami, & Kudo, ). In prevalently terrestrial urodeles of larger sizes (Scadding, ; Scadding, ; Alibardi, unpublished observations on Salamandra salamandra ), in caecilians, in anurans after metamorphosis (Figure ), in the following amniotes (Figure g,h), tissue and organ proliferation can no longer give rise to a morphogenetic process of regeneration. However, in small species of urodeles living in very humid and warm condition, such as the plethodontid salamander Bolitoglossa ramosi , a slow process of regeneration has been reported (Arenas‐Gomez, Gomez‐Molina, Zapata, & Delgado, ).…”
Section: Regeneration In Vertebrates Requires the Formation Of Blastemasmentioning
confidence: 99%
“…Urodele amphibians, including the axolotl Ambystoma mexicanum, possess a remarkable capacity for epimorphic limb regeneration (Scadding, 1981;Wallace, 1981). Following limb amputation, all limb structures which lie distal to the plane of amputation are regenerated, so that the complete limb is restored (Niazi and Saxena, 1978;Maden, 1983).…”
Section: Introductionmentioning
confidence: 99%